(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
The aim of the research was to explain the effectiveness of village administration in Molobog village of Motomgkad district of East Bolaang Mongondow. The study uses qualitative approach methods. The informant is one person as the head of the village, four as a village officer/device, and four people as a whole society as much as 9 Informans. Data collection using interview guidelines, while the analytical techniques used are interactive model analyses of Miles and Hubernan. Based on the results of analysis of data drawn conclusions: The aim of this research is to explain the effectiveness of village administration in Molobog village of Motomgkad district of East Bolaang Mongondow. Based on the results of the research that has been done by the author, it can be concluded as follows: (1) Production or realization of programs and government activities of Molobog village of Motomgkad regency of East Bolaang Mongondow Which is planned or about the work of the government of Molobog villages Motomgkad district of East Bolaang Mongondow in administration is already very good. According to the work or task given with the ability of the village government employees in the administrative administration with guidance on the regulation or regulation of government that has been established and administrative guidelines. (2) The efficiency or accuracy of the use of organizational resources, especially human resources and the cost in achieving the realization of the program and activities Pemerinah the village that has been planned/determined already showed excellent timeliness this is facilitated Because of the innovations that the village government has. (3) Adaptation or flexibility in this case the ability of the village government in response to the development of tasks/employment or in the face/handling of issues that arise already good. The ability to adapt the village government apparatus with the working environment and good organization to produce a working relationship between the employer and co-workers as well as attitudes and relationships to the recipient community is very well established service. Keywords: Effectiveness, implementation of village administration